Max : a Maximum Ride novel - Patterson, James, 1947- (Maximum Ride, 2009)
When millions of fish start dying off the coast of Hawaii and something is destroying hundreds of ships, the government enlists the Flock--a band of genetically modified children who can fly--to help get to the bottom of the disaster before it is too late.